Couple Stress Fluid Flow in A Doubly Connected Region Bounded by Elliptic Cylinders - Ramarao, Indira; Pramod, S.; Jagadeesha, S.; Rashmi, K. R.; Sreegowrav, K. R. (Communications in Mathematics and Applications, 2023)
A doubly connected region formed by confocal elliptic cylinders is considered. The cylinder walls are assumed to be impermeable, and rigid and fully developed flow of couple-stress fluid between the cylinders is considered. Conformal mapping of the form \(z = c(ζ+λζ)\) is applied \(x\)-\(y\) plane to \(ξ\)-\(η\) plane to transform elliptical cylinders into concentric circular cylinders. The governing equations are solved analytically in \(ξ\)-\(η\) plane using the Frobenius method. The solution obtained is numerically evaluated and graphically depicted.